Travelling Wave Solutions to the Zhiber-Shabat and Related Equations Using Rational Hyperbolic Method (Advances in Applied Mathematics and Mechanics, 2010)
This paper presents the application of a new method for obtainingnew exact solutions of some well-known nonlinear partialdifferential equations. The Rational Hyperbolic method is used forhandling the Zhiber-Shabat equation and the related equations suchas Liouville, Sinh-Gordon, Dodd-Bullough-Mikhailov andTzitzeica-Dodd-Bullough equations. We show power of the RationalHyperbolic method that is simple and effective for solving nonlinearpartial differential equations.